2014
DOI: 10.1128/jvi.03353-13
|View full text |Cite
|
Sign up to set email alerts
|

A Conformational Transition Observed in Single HIV-1 Gag Molecules during In Vitro Assembly of Virus-Like Particles

Abstract: The conformational changes within single HIV-1 Gag molecules that occur during assembly into immature viruses are poorly understood. Using an in vitro assembly assay, it has been proposed that HIV-1 Gag undergoes a conformational transition from a compact conformation in solution to an extended rod-like conformation in virus-like particles (VLPs). Here we used singlemolecule Förster resonance energy transfer (smFRET) to test this model by directly probing the conformation of single HIV-1 Gag molecules. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…2c and d), compact Gag oligomers can already form in the cytoplasm and do not undergo important structural changes at the PM. However, our data do not allow discriminating between the bent and extended conformations of Gag proteins [3,53], since closely packed oligomers may likely form with both conformations.…”
Section: Discussionmentioning
confidence: 94%
“…2c and d), compact Gag oligomers can already form in the cytoplasm and do not undergo important structural changes at the PM. However, our data do not allow discriminating between the bent and extended conformations of Gag proteins [3,53], since closely packed oligomers may likely form with both conformations.…”
Section: Discussionmentioning
confidence: 94%
“…This hypothesis is supported by the multivalent nature of NC, which allows it to bind at the same time two nucleic acid molecules (110). These differences between the relative stabilities of the different complexes, together with the ability of NC and NC/nucleic acid complexes to interact with negatively charged lipid membranes, lead us to revisit the HIV-1 assembly model, previously proposed by several groups (55,61,70,111) (for reviews, see references 59, 60, and 63). In this revised model, we propose that the NC domain of Gag participates in a transient manner in the binding of Gag to the PM, allowing the recruitment of negatively charged lipids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5, step 1), which is facilitated by the globular or bent conformation of Gag (36,55,59,61,62,69,70,112). At this stage, the binding of the gRNA to GagMA is thought to be mediated by the HBR sequence of Gag (61,64), while the myristyl group is still buried in the GagMA core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggested that Gag is initially folded and more compact, and upon membrane interactions forms an extended conformation necessary for oligomerization. Single-molecule FRET experiments supported this model, again suggesting that there is a conformational switch to an extended conformation that may be triggered by MA interactions with phosphoinositides at the plasma membrane, promoting subsequent oligomerization [58]. These in vitro and single molecule experiments are consistent with cell-based experiments in which three components appear essential to successful particle assembly: membrane interactions (including a role for myristoylation), NC-RNA interactions, and direct Gag-Gag interactions [5960].…”
Section: Gag and Hiv-1 Particle Assemblymentioning
confidence: 97%